PWE-087 Endoscopic Non-Ablative Radio Frequency Energy Treatment (Stretta®) for Gastro-Oesophageal Reflux Disease – The First UK Single Centre Experience. (17th August 2016) - Punnoose, S; Sathasivam, R; Reece-Bolton, O; Thambi, P; Dhar, A; Viswanath, Y
Abstract : Introduction: Gastro-oesophageal reflux disease (GORD) is usually treated with lifestyle modifications, combined with drug therapy (antacids, alginates and acid suppression drugs such as proton pump inhibitors and H2 receptor antagonists). Patients with inadequate response to lifestyle and medical treatments, or intolerant of medical therapy, are offered anti-reflux surgery with open or laparoscopic fundoplication which remains the gold standard. 1, 2 Stretta® is a minimally-invasive endoscopic treatment that delivers non-ablative radiofrequency (NARF) energy to improve and restore the function of the lower oesophageal sphincter muscle, thereby improving symptoms of GORD. The efficacy of the Stretta® procedure in achieving symptom control of GORD has been reported in previous international publications. A systematic review involving 20 studies with 1441 patients having a mean follow-up interval of 15 months showed significant improvements in GORD symptoms including disease-specific and global quality of life. 3 UK data on the outcomes of Stretta® have not been reported, and this is the first report of the Stretta® procedure in the UK, carried out at a single centre since October 2014. Methods: Patients with confirmed GORD, unresponsive to medical management with standard or double dose PPI, were offered the Stretta ®procedure based on clinician and patient shared decision. Patients with an associated hiatus hernia of ≤2 cm on their index endoscopy were included. Patients needed to be symptomatic of reflux for at least 3 months on medication and all patients were administered a GERD Health Related Quality of Life (GERD-HRQL) questionnaire pre- and post-Stretta® procedure. The Stretta ® procedure was carried out either under general anaesthesia (early phase) or conscious sedation (later phase) by a single trained endoscopist using the manufacturers protocol. Up to 14 lesion sets or 56 RF applications to the LOS at 1 cm intervals were carried out using an automated generator (Mederi Therapeutics Inc, USA). Results: 26 patients underwent the Stretta procedure over a period of 12 months (October 2014 - September 2015).The mean follow-up period was 3.8 months (range 10.5) and there were no recorded procedural complications. All patients completed pre and post procedure GERD-HRQL questionnaires. The median heartburn score (scale 0–30) improved from 18 pre-procedure to 2.5 post-procedure. The overall median regurgitation score (scale 0–30) improved from 19 pre-procedure to 0 post procedure. The overall patient satisfaction was 78%. There was also an improvement in the median overall total GERD-HRQL score (scale 0–75) from 44 pre-procedure to 6 post-procedure. 3 patients had undergone previous anti-reflux surgery. There was again overall improvement of median heartburn scores (18 pre, 0 post), regurgitation scores (1 pre, 0 post) and total GERD-HRQL scores (27 pre, 0 post). Baseline and post-procedure GERD-HRQLscores in 27 patients, average follow-up of 3.8 months: Conclusion: In this first UK report of Stretta, we demonstrate therapeutic benefit in medically non-responsive GORD, improving patient's heartburn, regurgitation and overall satisfaction scores with low procedural risks. There is also therapeutic benefit in patients with recurrent reflux symptoms after previous anti-reflux surgery, making it a possible treatment option for this group of patients. A larger UK Study is needed to incorporate Stretta into the therapeutic pathway for GORD. Reference: 1 Kyle A, Perry MD, Ambar Banerjee MD, William Scott Melvin MD. Radiofrequency Energy Delivery to the Lower Oesophageal Sphincter Reduces Oesophageal Acid Exposure and Improves GERD Symptoms: A Systematic Review and Meta-analysis. Surgical Laparoscopy, Endoscopy and Percutaneous Techniques 2012;22 :283–88. Disclosure of Interest: S. Punnoose: None Declared, R. Sathasivam: None Declared, O. Reece-Bolton: None Declared, P. Thambi: None Declared, A. Dhar Grant/research support from: Takeda, Shire, Abbvie, Consultant for: Takeda, Abbvie, Y. Viswanath: None Declared